Inclusions in a Single Variable in Ultrametric Spaces and Hyers-Ulam Stability - Magdalena Piszczek (The Scientific World Journal)
We present some properties of set-valued inclusions in a single variable in ultrametric spaces. As a consequence, we obtain stability results for the corresponding functional equations.